2011
DOI: 10.1002/art.30114
|View full text |Cite
|
Sign up to set email alerts
|

An oral Syk kinase inhibitor in the treatment of rheumatoid arthritis: A three‐month randomized, placebo‐controlled, phase II study in patients with active rheumatoid arthritis that did not respond to biologic agents

Abstract: Objective. To assess the efficacy and safety of R788 (fostamatinib disodium), an inhibitor of spleen tyrosine kinase (Syk), in patients with active rheumatoid arthritis (RA) that did not respond to biologic therapies.Methods. A total of 219 patients with active RA in whom treatment with biologic agents had failed were enrolled in a 3-month multicenter, randomized, doubleblind, placebo-controlled trial of R788. The primary end point was the percentage of patients who met the American College of Rheumatology 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 13 publications
8
132
0
3
Order By: Relevance
“…The OSKIRA clinical trial program was initiated after the results of 2 phase II clinical studies demonstrated that treatment with fostamatinib significantly reduced the signs and symptoms of RA (7,8) (a third phase II clinical study in patients who had failed treatment with anti-TNF␣ agents, however, found no significant difference in the proportion of patients achieving an ACR20 improvement response at month 3 [study primary end point] between the fostamatinib and placebo groups [17]). …”
Section: Discussionmentioning
confidence: 99%
“…The OSKIRA clinical trial program was initiated after the results of 2 phase II clinical studies demonstrated that treatment with fostamatinib significantly reduced the signs and symptoms of RA (7,8) (a third phase II clinical study in patients who had failed treatment with anti-TNF␣ agents, however, found no significant difference in the proportion of patients achieving an ACR20 improvement response at month 3 [study primary end point] between the fostamatinib and placebo groups [17]). …”
Section: Discussionmentioning
confidence: 99%
“…Notably, both these studies included a significant proportion of patients who had failed biological therapy with anti-TNF or anti-CD20 agents, and benefit with fostamatinib was seen in these subgroups (although overall response rates were lower than for the whole study population). A subsequent trial designed specifically to examine the efficacy of fostamatinib in this group of patients failing biologic therapy, however, did not achieve its primary endpoint of improved ACR20 in the treatment group (Genovese, Kavanaugh et al 2011). There were, however, significant improvements in radiographic and biochemical markers of inflammation.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…Accordingly, several drugs, targeting these kinases have been recently tested in patients suffering from severe auto-inflammation (Grimminger et al, 2010;Laudisi et al, 2014). Meanwhile a promising candidate (PRT062607, Biogen Idec, Cambridge, MA, USA) is under evaluation, previous Syk inhibitors, such as AstraZeneca, R-788, showed low specificity and high toxicity, which forced to abandon their development (Genovese et al, 2011;Flight, 2012). Regardless, Hara and colleagues have showed that specific inhibition of phosphorylated ASC could represent an alternative means to enable suppression of caspase-1 activation and the associated pathological consequences (Laudisi et al, 2014).…”
Section: Therapeutic Implications Of Aim2 Inflammasomementioning
confidence: 99%